A systematic review of the presence of bovine coronavirus on environmental surfaces - Furlan, Carla Regina Costa; Weber, Saulo Henrique; Sanches, Gustavo Seron [UNESP]; Agnol, Alais Maria Dall; Ollhoff, Rüdiger Daniel; Sotomaior, Cristina Santos (FapUNIFESP (SciELO), 2025)
The main transmission route of bovine coronavirus (BCoV) is direct contact with secretions and feces, and potentially also via contaminated surfaces. Following PRISMA guidelines, a systematic review was conducted to evaluate the presence of BCoV on environmental surfaces. A literature search, conducted between March and April 2023, utilized databases including Web of Science, PubMed, Scopus, Science Direct, and Springer. The review adhered to the PEO structure: Population-environmental surfaces; Exposure-contact with BCoV; Outcome-identification of presence or infectivity. Primary data were recorded using an extraction form organizing methods for detecting BCoV presence, assessing BCoV infectivity, types of surfaces evaluated, and study type. Search terms “Bovine coronavirus” and “BCoV” yielded 2703 articles. After removing 964 duplicates and excluding 1546 articles not mentioning BCoV in titles, 193 studies underwent abstract reading. Following exclusion criteria not addressing BCoV presence in the environment, three articles were selected for comprehensive review. These articles identified BCoV presence on various types of surfaces, with detection possible up to 81 hours after contamination, depending on surface type. Despite limited studies on BCoV presence on surfaces, findings suggested potential transmission via contaminated surfaces due to the virus’s ability to remain infectious for up to 24 hours on fomites. This review underscores the need for further research on BCoV persistence in farm environments, an area currently lacking focused studies.
Revisão sistemática da presença de coronavírus bovino em superfícies ambientais
Keywords: BCoV; cattle; environment contamination; infectivity; transmission routes